The Yaws handbook of physical properties for hydrocarbons and chemicals physical properties for more than 54,000 organic and inorganic chemical compounds, coverage for C1 to C100 organics and Ac to Zr inorganics - Yaws, Carl L. (Amsterdam : Elsevier, 2015)
Refineries and petrochemical engineers today are accepting more unconventional feedstocks such as heavy oil and shale, causing unique challenges on the processing side of the business. To create more reliable engineering design of process equipment for the petrochemical industry, petroleum engineers and process managers are forced to study the physical properties and compounds of these particular hydrocarbons. Instead of looking up each compound's information, The Yaws Handbook of Physical Properties for Hydrocarbons and Chemicals, Second Edition presents an easy-to-use format with rapid access to search for the particular compound and understand all the complex calculations in one tabular format. Understanding the composition of hydrocarbons is not easy to calculate quickly or accurately, but this must-have reference leads the engineer to better estimated properties and fractions from easily measured components. Expanded to cover more total compounds and relevant functions, The Yaws Handbook of Physical Properties for Hydrocarbons and Chemicals, Second Edition remains a necessary reference tool for every petrochemical and petroleum engineers' library.
Cover; Title Page; Copyright Page; Contents; Contributors; Acknowledgments; Disclaimer; About the Authors; Chapter 1 -- Physical Properties -- Organic Compounds; Example; Keywords; Chapter 2 -- Physical Properties -- Inorganic Compounds; Example; Chapter 3 -- Properties -- Water; Example; Chapter 4 -- Properties -- Air; Example; References; Index.
Includes bibliographical references and index.
Description from online resource; title from PDF title page (viewed February 17, 2015).
Elsevier
Keywords: Chemicals -- Handbooks, manuals, etc; Hydrocarbons -- Handbooks, manuals, etc; Chemicals -- Tables; Hydrocarbons -- Tables; SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Chemicals; Hydrocarbons; Electronic books; Handbooks and manuals; Tables; Electronic books